USER EXPERIENCE (UX) AND USER INTERFACE (UI) DESIGN FOR E-GOVERNMENT SERVICES IN EAST KALIMANTAN: ENHANCING PUBLIC SERVICE ADOPTION THROUGH USER-CENTERED DESIGN - Mundzir Mundzir (Multica Science and Technology (ACCREDITED-SINTA 5), 2025)
This study investigates how user-centered User Experience (UX) and User Interface (UI) design influence the adoption of e-government services in East Kalimantan, Indonesia. Despite efforts to digitize public services, citizen engagement with these platforms remains low, often due to usability issues. Employing a qualitative descriptive approach grounded in the User-Centered Design (UCD) framework, data were collected through semi-structured interviews, direct user observations, and policy document analysis. Thematic analysis using NVivo revealed key pain points such as inconsistent interface design, cognitive overload, poor error recovery, and low user trust. Quantitative insights from observational data highlighted that task abandonment often occurred at CAPTCHA verification and form submission stages. The findings emphasize the importance of integrating UX/UI design principles, including heuristic evaluation and participatory design, into the development of digital public services. This study contributes to the discourse on e-government by demonstrating that citizen-centered design is crucial not only for improving service usability but also for fostering public trust and long-term adoption. Future work should focus on the development of standardized UX frameworks for regional governments to ensure inclusive, accessible, and responsive digital services.